Risk factors associated with calf mortality from birth to weaning in pasture-based dairy herds in Argentina - Welschen, Nicolas Mario; Alvarado, Wanda; Miotti, Camila; Peña, Agostina; Zbrun, María Virginia; Signorini Porchiett, Marcelo Lisandro; Molineri, Ana Ines (Elsevier, 2025)
The aim of this study was to 1) estimate dairy calf mortality from birth to weaning in Argentinean herds, and 2) identify associated risk factors. A cross-sectional study was conducted between November 2019 and March 2020 in one of Argentina's most important dairy regions. A total of 77 dairy farms were included in the study. Potential explanatory variables were obtained from a checklist questionnaire answered by calf nursers. Dairy calf mortality was modelled using a generalized linear model applying a binomial distribution (number of calves that died in the previous year / total number of calves born alive during the last year) and logistic link function. The mean calf mortality was 10.1 % (95 %CI 9.6–10.6 %). The associated risk factors of calf mortality were work experience, navel disinfection, climate protection, colostrum management, weaning decisions, the number of calf nursers, and the ratio of live-born calves per cow. Calf mortality is higher when there is less work experience (Odds Ratio -OR- = 6.25; 95 %CI 4.17–10), no navel disinfection is performed (OR = 1.75; 95 %CI 1.50–2.02), there is less climate protection (extreme weather protection of the calves, OR = 1.66; 95 %IC 1.40–1.19), colostrum management is poor (OR = 2.17; 95 %IC 1.64–2.94), weaning is based on calf´s size (OR = 1.22; 95 %IC 1.05–1.41), there is a reduced number of calf nursers (OR = 0.84; 95 %CI 0.75–0.95), and the ratio of live-born calves per cow is low (OR = 0.63; 95 %CI 0.38–1.06). In summary, the mortality risk of dairy calves in Argentina was associated with different aspects related to the calf nursers (number and work experience), calving management (colostrum management, weaning method, climate protection, and navel disinfection), and the efficiency of the dairy farm (ratio of live-born caves per cow).